ANALISIS KESALAHAN SISWA KELAS X DALAM MENYELESAIKAN SOAL MATERI FUNGSI KUADRAT BERDASARKAN PROSEDUR KASTOLAN - Yeni Kurniasari; Asep Ikin Sugandi; Ratna Sariningsih (IKIP Siliwangi, 2021)
The research that has been conducted on students of class X SMA Negeri 1 Sindangbarang aims to analyze errors in working on quadratic function questions. Using a qualitative descriptive method, the data were taken from the answers of 6 high school class X students. Instruments in the form of questions about the material description of quadratic functions as many as 5 items of Bloom's taxonomy questions that have been validated. Data analysis methods in this study are data reduction, data presentation, and verification. Errors made by students when working on quadratic function questions based on Kastolan procedures include: (1) conceptual errors of 40%, which are included in the heavy category; (2) procedural errors of 35% in the moderately severe category; and (3) 25% technical error, which is included in the light category.